1976
DOI: 10.1083/jcb.70.1.123
|View full text |Cite
|
Sign up to set email alerts
|

The contractile basis of ameboid movement. II. Structure and contractility of motile extracts and plasmalemma-ectoplasm ghosts.

Abstract: The role of calcium and magnesium-ATP on the structure and contractility in motile extracts of Amoeba proteus and plasmalemma-ectoplasm "ghosts" of Chaos carolinensis has been investigated by correlating light and electron microscope observations with turbidity and birefringence measurements. The extract is nonmotile and contains very few F-actin filaments and myosin aggregates when prepared in the presence of both low calcium ion and ATP concentrations at an ionic strength of I = 0.05, pH 6.8. The addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
77
0

Year Published

1976
1976
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 35 publications
9
77
0
Order By: Relevance
“…In common with Acantharnoeba (22, 23), macrophages (28,29), leukemic cells (4), sea urchin eggs (15,16), and giant amebas (31), suitable extracts of HeLa cells can form a gel. In all cases, gelation can be related to a polymerization of actin induced by warming, but the generality of the role of the other proteins which have been isolated with gels is less well established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In common with Acantharnoeba (22, 23), macrophages (28,29), leukemic cells (4), sea urchin eggs (15,16), and giant amebas (31), suitable extracts of HeLa cells can form a gel. In all cases, gelation can be related to a polymerization of actin induced by warming, but the generality of the role of the other proteins which have been isolated with gels is less well established.…”
Section: Discussionmentioning
confidence: 99%
“…The gels formed by three of these cytoplasmic extracts can shrink spontaneously (4,22,29), and the incorporation of myosin into the shrunken gels has suggested that interactions of actin and myosin induce gel shrinkage. These newer observations on gelation and shrinkage seem to be related to the older observations on consistency changes and movement of ameba extracts by the observation of a gel-like consistency for the ameba cytoplasm un-der certain conditions (31) and the apparent involvement of actin and myosin in both sorts of systems. I previously reported that suitable extracts of HeLa cells undergo a gelation reaction, which can be related to actin and a high molecular weight protein (HMWP) (34,35).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Motile extracts of these cells exhibit viscosity changes in vitro (23,33,35,37) and have been used to advantage in studying structural transformations at a molecular level. Experimental evidence linking consistency changes in vitro with the assembly and interaction of contractile protein filaments (11,23,24,33,34) has suggested that the J. CELL BIOLOGY 9 The Rockefeller University Press 9 0021-9525/78…”
Section: Abstract Actin Gelation Contraction Calciummentioning
confidence: 99%